Measuring value creation and appropriation in firms: The VCA model - Lieberman, Marvin B.; Garcia‐Castro, Roberto; Balasubramanian, Natarajan (Strategic Management Journal, 2017)
Research summary : Using a productivity technique (VCA model), we estimate the economic value created by a firm and appropriated by its stakeholders in two specific empirical contexts. In the first application, we use publicly available data from the U.S. airline industry to illustrate how the VCA model can be used with multiple stakeholder groups. In the second application, we provide estimates for three global automobile companies (GM, Toyota and Nissan), showing how the model can be reformulated using value added. In both industries we find substantial heterogeneity among firms in the creation and distribution of value. We discuss strengths and limitations of the VCA model and implications for strategic management research. Managerial summary : Firms create value not only for shareholders, but also for other stakeholders, including employees, customers and suppliers. This article applies a method to quantify the “new” economic value created by a firm over an interval of time; the method also reveals the distribution of that value among the stakeholders. The proposed method gives managers some means to assess changes in the economic value created and distributed. We find that the creation and distribution of value has varied greatly among major U.S. airlines and global automakers in recent decades. Moreover, returns to shareholders typically accounted for only a small proportion of firms' total value creation and often had little relation to broader changes in the magnitude and distribution of value . Copyright © 2016 John Wiley & Sons, Ltd.